Vermittlerstrategien und Arbeitsmarkterfolg – Evidenz aus kombinierten Prozess- und Befragungsdaten - Bernhard Boockmann; Christopher Osiander; Michael Stops (Journal for Labour Market Research, 2014)
– In spite of extensive regulations, Germany's job offices and their caseworkers have substantial discretion in implementing labor market policies. Based on the analysis of combined survey and administrative data, this study compares the effectiveness of different strategies aimed at re-integrating job seekers in the unemployment insurance system (Social Code III) into regular employment. The data merger is an innovative contribution of our paper, since it is done for the first time for German data. Most of the estimated treatment effects are moderate in size and statistically significant only for parts of the unemployment duration. We find that caseworkers who emphasize rapid integration into work as their primary goal tend to achieve better results for their clients than caseworkers who consider other goals important. While the willingness to impose sanctions weakly significantly increases the probability to leave unemployment, it does not have a positive impact on the probability to find employment. Furthermore, frequent contacts between caseworker and job seeker tend to have positive effects in terms of exit from unemployment. Finally, caseworkers who consider internal regulations important when they allocate job seekers to programs of ALMP tend to achieve better integration outcomes at the beginning of clients' unemployment spells.
Keywords: J08; J64; J68; 330; Arbeitsvermittlung - Erfolgskontrolle; Vermittlungserfolg; Arbeitsvermittler - Einstellungen; Arbeitslose; berufliche Reintegration; Sozialgesetzbuch III; Beschäftigungseffekte; Vermittlungsprozess; Case Management; Sanktion; Prozessorientierung; Eingliederungsbilanz; matching; Integrierte Erwerbsbiografien; Handlungsspielraum